Hybridity: an urban response to a crisis of identity sameness - Bruyns, Elizabeth Claire (My University, 2010)
Architectural character is currently facing a crisis of sameness, as individual regional architectural identities are being subsumed into a greater global capitalist culture. This is resulting in loss of diversity and difference in urban life. With the dominance of commercial development in urban environments around the world, there is a disproportionate relationship between public and private space. The general public is being forced to operate solely within the private realm. This essay discusses this phenomenon, recently referred to as McDonaldisation. While many architects design utopian cities and lifestyles, few have undertaken the task of developing these concepts into realistic projects. This study attempts to bridge this gap between architectural idealism and social reality by developing a hybrid architectural outcome that improves social conditions while simultaneously facilitating commercial practice and the need for profitability in architecture. A review of architectural and sociopolitical literature reveals the necessity of approaching this debate from a multiperspectivist viewpoint for the creation of hybrid theoretical and architectural responses which engage with the everyday. This paper describes briefly the history of hybrids and examines three case studies of mixed-use buildings to more clearly illustrate the meaning of the term hybrid, in the architectural context. A solution is posed to this problem through the creation of new hybridised development models which engage the public realm on a substantive level.